Peran Media Sosial Dalam Membantu Usaha Kecil Dalam Berjualan Online - Fasrian Mauren Niella Hura; Elsya Dwi Indah Hura (CV. SINAR HOWUHOWU, 2024)
The focus of this reseacrh focuses on the problems of the relationship between social media and business that will affect the development of online shop businesses both partially and simultaneously. This research aims to determine the effect of social media and business communication on the development of online shop business. The subject of this research is online shop users on social media. This research using quantitative descriptive research and the instrument used is a questionnaire. Data analysis techniques used quantitative descriptive data analysis. The validity of the data is obtained through validity and reliability. The results showed that: (1) there was a positive and significant influence between social media and the development of online shop business by 62% which was seen from the value of tcount = 2.205 (>table = 1.664), at 5% significance, (2) positive and significant between business communication and online shop business development by 76% which is seen from the value of tcount = 3.258 (> ttable = 1.664), at 5% significance, and (3) there is a positive and significant influence between social media, business communication the development of online shop business is 88% which is seen from the value of F count = 10,556 (> Ftable = 1,980) at a significance of 5%.